DEMOGRAPHIC CHANGE AND ITS IMPACT ON FISCAL GOVERNMENT IN INDONESIA - Salman Samir; Achmad Rifa’i; Listiono Listiono; Irwandi Irwandi; Maizul Rahmizal (Hasanuddin Economics and Business Review, 2017)
Indonesia experiences demographic change because of basically the result of successful policies in the past. Especially in the health sector where in the era of Orde Baru[1] the family planning program was successfully implemented. Productive age over non productive age are the two main variables in addition to some other variables that are also shaping demographic change. This study highlighted the demographic changes, particularly with the increasing burden of government dependents in the allocation of education, health, and social security. This study attempted to see the effect of demographic change on government fiscal using the Error Correction Model. The choice of this model was because ECM could be used to see the short-run dynamic relationship of variables that have cointegration relationship. The results showed that there are cointegration so that it could be continued by estimating using ECM and the results show that demographic change have an influence on government fiscal where proxies used such as mortality, birth rate, life expectancy have significant effect while productive and non-productive age have no significant effects.Â [1] Orde Baru is Period when Soeharto occupied as The 2nd President of Indonesia